Media Flashcard untuk Mendukung Pengenalan Huruf Anak Usia 5–6 Tahun di Aisyiyah Bustanul Athfal III - Nonita Hajra; Credo G. Betty; Yohana Yuniati; Kamelia Olga Litna (BOCAH: Borneo Early Childhood Education and Humanity Journal, 2026)
This study aims to describe the use of flashcard media in supporting letter recognition skills among children aged 5–6 years at TK Aisyiyah Bustanul Athfal III. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The research participants consisted of the school principal, the B1 classroom teacher, and four children aged 5–6 years, purposively selected based on initial observations because their letter recognition skills had not yet developed optimally. The findings show that flashcard media was used gradually, repeatedly, systematically, and through enjoyable, play-based activities that were appropriate to the characteristics of early childhood learners. The use of flashcard media supported children’s active participation in learning activities, including paying attention to letter cards, identifying letter symbols, matching letters to pictures, grouping pictures by the same initial sounds, and gradually reading and writing their own names. However, several children still required additional guidance and repeated instruction from the teacher because each child’s developmental progress varied. Therefore, flashcard media can be used as an alternative learning medium to support letter recognition skills in early childhood education.